3-D numerical simulation of an automotive air intake system: A study of the Ford Ka 2015 case. (November 2019) - de Melo Filho, A.R.V.; da Cunha Lima, A.T.; da Cunha Lima, I.C.
Abstract: An analysis of the air flow through an automotive air intake system considers the effects of the external temperature and the performance decay by time of usage. The domain of the simulation corresponds to the geometry of a physical component applied to a commercial vehicle, the 2015 model year of the Ford Ka, after advanced three-dimensional scanning tools. A porous region inside the air intake system comprises the air filter, and is the center of analysis in this calculation. The numerical solution of the Navier-Stokes equation is modeled in the Fluent® software.